Music induced happy mood suppresses the neural responses to other's pain: Evidences from an ERP study. Issue 1 (December 2017) - Cheng, Jiaping; Jiao, Can; Luo, Yuejia; Cui, Fang
Abstract In the current study, we explored the time course of processing other's pain under induced happy or sad moods. Event-related potentials (ERPs) were recorded when participants observing pictures showing others in painful or non-painful situations. Mood induction procedures were applied to the participants before the picture observation task. Happy and sad moods were induced by listening to about 10 minutes of music excerpts selected from the Chinese Affective Music System (CAMS). The ERP results revealed that the induced mood can influence the early automatic components N1, P2, and N2 but not the later top-down controlled components P3 and LPP. The difference of amplitudes elicited by painful and non-painful stimuli was significantly different only in a sad mood but not in a happy mood, which indicates that comparing to a sad mood, the participants' ability to discriminate the painful stimuli from the non-painful stimuli was weakened in a happy mood. However, this reduction of sensitivity to other's pain in a happy mood does not necessarily reduce the tendency of prosocial behaviors. These findings offer psychophysiological evidences that people's moods can influence their empathic response towards other's pain.